On the Analysis of Field Patterns in Chirofibers - Nair, A.; Choudhury, P. K. (VSP BV, BRILL ACADEMIC PUBLISHERS, 2007)
The paper presents a rigorous analytical approach to determine the field patterns in simple chirofibers having circular cross-section. Variations in core as well as cladding chiralities are considered to investigate the behavioral feature of the fields propagating in the structure. In particular, the results are compared in two situations - varying core chirality with a fixed clad chirality; varying clad chirality with a fixed core chirality. In all situations, the effect of core/clad chiralities on the field patterns is reported.